Assessment of a deep learning model for algal toxin forecasting in coastal Maine - Johnathan Evanilla; Nicholas R. Record; Benjamin Tupper; Bryant Lewis; David W. Miller; Kohl Kanwit; Craig Burnell; Stephen D. Archer (Harmful Algae, 2026)

Leveraging Remote Sensing and Theory to Predict Tree Size Abundance Distributions Across Space - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; J. Marcos Rodriguez; Ben Weinstein; David A. Orwig; Sydne Record (Global Ecology and Biogeography, 2025)
Background Remote sensing (RS) technologies provide unprecedented opportunities to assess forest structure at broad spatial scales. Light detection and ranging (LiDAR) is a powerful tool that offers detailed vertical information, but its consistent high‐resolution coverage can be limited across vast areas and quantifying understory vegetation remains challenging due to occlusion. Conversely, while high‐resolution RGB imagery is more accessible and valuable for large‐scale analyses, it comes with higher uncertainty and only captures canopy‐level information. Integrating RGB data with ecological theory and existing LiDAR‐derived products (e.g., canopy height models, CHM) allows us to enhance predictions and broaden the applicability of forest size structure mapping from the understory to the canopy, particularly through tree size–abundance relationships. Theory Tree size and abundance generally follow known distributions, where smaller trees are exponentially more common than larger trees. This pattern emerges from fundamental ecological constraints, including volume packing, metabolic scaling and light competition, which collectively govern forest self‐organisation across spatial scales. Proposed Approach We present a workflow that integrates size‐abundance scaling theory with RGB data and CHMs to improve predictions of forest structure. By estimating tree size distributions from RGB imagery, we extend the applicability of ecological scaling models to broader spatial scales and offer an approach that complements traditional methods. Assessment We apply this approach to forest monitoring networks, including NEON and ForestGEO, to assess its accuracy and generalisability across a range of forests (e.g., subtropical pine, boreal, low and dry, tall and dense) in North America. Our results show that RGB‐based estimates can successfully recover size‐abundance distributions from the understory to the canopy. Future Directions Further refinement of our approach could enhance predictions by incorporating species classifications from hyperspectral data and using more spatially or taxonomically specific allometric equations. These additions would enable more precise scaling of tree diameter from remote sensing data.

Responses to and detoxification of esculin in white-rot fungi - Raphael Bchini; Sylvain Darnet; Arthur de Butler; Annick Doan; Lydie Oliveira-Correia; David Navarro; Eric Record; Mélanie Morel-Rouhier (Fungal Biology, 2024)

Large protistan mixotrophs in the North Atlantic Continuous Plankton Recorder time series: associated environmental conditions and trends - Karen Stamieszkin; Nicole C. Millette; Jessica Y. Luo; Elizabeth Follett; Nicholas R. Record; David G. Johns (Frontiers in Marine Science, 2024)
Aquatic ecologists are integrating mixotrophic plankton – here defined as microorganisms with photosynthetic and phagotrophic capacity – into their understanding of marine food webs and biogeochemical cycles. Understanding mixotroph temporal and spatial distributions, as well as the environmental conditions under which they flourish, is imperative to understanding their impact on trophic transfer and biogeochemical cycling. Mixotrophs are hypothesized to outcompete strict photoautotrophs and heterotrophs when either light or nutrients are limiting, but testing this hypothesis has been hindered by the challenge of identifying and quantifying mixotrophs in the field. Using field observations from a multi-decadal northern North Atlantic dataset, we calculated the proportion of organisms that are considered mixotrophs within individual microplankton samples. We also calculated a “trophic index” that represents the relative proportions of photoautotrophs (phytoplankton), mixotrophs, and heterotrophs (microzooplankton) in each sample. We found that the proportion of mixotrophs was positively correlated with temperature, and negatively with either light or inorganic nutrient concentration. This proportion was highest during summertime thermal stratification and nutrient limitation, and lowest during the North Atlantic spring bloom period. Between 1958 and 2015, changes in the proportion of mixotrophs coincided with changes in the Atlantic Multi-decadal Oscillation (AMO), was highest when the AMO was positive, and showed a significant uninterrupted increase in offshore regions from 1992-2015. This study provides an empirical foundation for future experimental, time series, and modeling studies of aquatic mixotrophs.

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Experimental and observational evidence of negative conspecific density dependence in temperate ectomycorrhizal trees - Fiona V. Jevon; Dayna De La Cruz; Joseph A. LaManna; Ashley K. Lang; David A. Orwig; Sydne Record; Paige V. Kouba; Matthew P. Ayres; Jaclyn Hatala Matthes (Ecology, 2022)
Conspecific negative density dependence (CNDD) promotes tree species diversity by reducing recruitment near conspecific adults due to biotic feedbacks from herbivores, pathogens, or competitors. While this process is well‐described in tropical forests, tests of temperate tree species range from strong positive to strong negative density dependence. To explain this, several studies have suggested that tree species traits may help predict the strength and direction of density dependence: for example, ectomycorrhizal‐associated tree species typically exhibit either positive or weaker negative conspecific density dependence. More generally, the strength of density dependence may be predictably related to other species‐specific ecological attributes such as shade tolerance, or the relative local abundance of a species. To test the strength of density dependence and whether it affects seedling community diversity in a temperate forest, we tracked the survival of seedlings of three ectomycorrhizal‐associated species experimentally planted beneath conspecific and heterospecific adults on the Prospect Hill tract of the Harvard Forest, in Massachusetts, USA. Experimental seedling survival was always lower under conspecific adults, which increased seedling community diversity in one of six treatments. We compared these results to evidence of CNDD from observed sapling survival patterns of 28 species over approximately 8 years in an adjacent 35‐ha forest plot. We tested whether species‐specific estimates of CNDD were associated with mycorrhizal association, shade tolerance, and local abundance. We found evidence of significant, negative conspecific density dependence (CNDD) in 23 of 28 species, and positive conspecific density dependence in two species. Contrary to our expectations, ectomycorrhizal‐associated species generally exhibited stronger (e.g., more negative) CNDD than arbuscular mycorrhizal‐associated species. CNDD was also stronger in more shade‐tolerant species but was not associated with local abundance. Conspecific adult trees often have a negative influence on seedling survival in temperate forests, particularly for tree species with certain traits. Here we found strong experimental and observational evidence that ectomycorrhizal‐associating species consistently exhibit CNDD. Moreover, similarities in the relative strength of density dependence from experiments and observations of sapling mortality suggest a mechanistic link between negative effects of conspecific adults on seedling and sapling survival and local tree species distributions.

Benefits and Challenges of a Stakeholder-Driven Shellfish Toxicity Forecast in Coastal Maine - Nicholas R. Record; Johnathan Evanilla; Kohl Kanwit; Craig Burnell; Carmen Cartisano; Bryant J. Lewis; Jill MacLeod; Benjamin Tupper; David W. Miller; Adrienne T. Tracy; Carol White; Matt Moretti; et al. (Frontiers in Marine Science, 2022)
Paralytic shellfish poison (PSP) is a human health concern for shellfish aquaculture and wild harvest. This paper discusses lessons learned from a forecasting program for PSP in coastal Maine, USA, designed based on stakeholder input, and run in an operational mode for the 2021 season. The forecast uses a deep learning algorithm to make site-specific, probabilistic forecasts at a weekly forecast range for toxin levels measured in shellfish tissue. Forecasts had high accuracy in the 2021 season, correctly predicting closure events and locations despite a highly unusual season. Stakeholders reported a positive view of the forecast system, and stakeholder input continues to be of key importance as further modifications are made to the system. There are benefits and challenges to the stakeholder-based design of the system.

Climate‐driven, but dynamic and complex? A reconciliation of competing hypotheses for species’ distributions - Emily L. Schultz; Lisa Hülsmann; Michiel D. Pillet; Florian Hartig; David D. Breshears; Sydne Record; John D. Shaw; R. Justin DeRose; Pieter A. Zuidema; Margaret E. K. Evans (Ecology Letters, 2022)
Estimates of the percentage of species “committed to extinction” by climate change range from 15% to 37%. The question is whether factors other than climate need to be included in models predicting species’ range change. We created demographic range models that include climate vs. climate‐plus‐competition, evaluating their influence on the geographic distribution of Pinus edulis , a pine endemic to the semiarid southwestern U.S. Analyses of data on 23,426 trees in 1941 forest inventory plots support the inclusion of competition in range models. However, climate and competition together only partially explain this species’ distribution. Instead, the evidence suggests that climate affects other range‐limiting processes, including landscape‐scale, spatial processes such as disturbances and antagonistic biotic interactions. Complex effects of climate on species distributions—through indirect effects, interactions, and feedbacks—are likely to cause sudden changes in abundance and distribution that are not predictable from a climate‐only perspective.

Anthropogenic climate change impacts on copepod trait biogeography - Niall McGinty; Andrew D. Barton; Nicholas R. Record; Zoe V. Finkel; David G. Johns; Charles A. Stock; Andrew J. Irwin (Global Change Biology, 2021)
Copepods are among the most abundant marine metazoans and form a key link between marine primary producers, higher trophic levels, and carbon sequestration pathways. Climate change is projected to change surface ocean temperature by up to 4°C in the North Atlantic with many associated changes including slowing of the overturning circulation, areas of regional freshening, and increased salinity and reductions in nutrients available in the euphotic zone over the next century. These changes will lead to a restructuring of phytoplankton and zooplankton communities with cascading effects throughout the food web. Here we employ observations of copepods, projected changes in ocean climate, and species distribution models to show how climate change may affect the distribution of copepod species in the North Atlantic. On average species move northeast at a rate of 14.1 km decade −1 . Species turnover in copepod communities will range from 5% to 75% with the highest turnover rates concentrated in regions of pronounced temperature increase and decrease. The changes in species range vary according to copepod traits with the largest effects found to occur in the cooling, freshening area in the subpolar North Atlantic south of Greenland and in an area of significant warming along the Scotian shelf. Large diapausing copepods (>2.5 mm) which are higher in lipids and a crucial food source for whales, may have an advantage in the cooling waters due to their life‐history strategy that facilitates their survival in the arctic environment. Carnivorous copepods show a basin wide increase in species richness and show significant habitat area increases when their distribution moves poleward while herbivores see significant habitat area losses. The trait‐specific effects highlight the complex consequences of climate change for the marine food web.

Mud, Microbes, and Macrofauna: Seasonal Dynamics of the Iron Biogeochemical Cycle in an Intertidal Mudflat - Jacob P. Beam; Sarabeth George; Nicholas R. Record; Peter D. Countway; David T. Johnston; Peter R. Girguis; David Emerson (Frontiers in Marine Science, 2020)

It’s about time: A synthesis of changing phenology in the Gulf of Maine ecosystem - Michelle D. Staudinger; Katherine E. Mills; Karen Stamieszkin; Nicholas R. Record; Christine A. Hudak; Andrew Allyn; Antony Diamond; Kevin D. Friedland; Walt Golet; Meghan Elisabeth Henderson; Christina M. Hernandez; Thomas G. Huntington; et al. (Fisheries Oceanography, 2019)
The timing of recurring biological and seasonal environmental events is changing on a global scale relative to temperature and other climate drivers. This study considers the Gulf of Maine ecosystem, a region of high social and ecological importance in the Northwest Atlantic Ocean and synthesizes current knowledge of (a) key seasonal processes, patterns, and events; (b) direct evidence for shifts in timing; (c) implications of phenological responses for linked ecological‐human systems; and (d) potential phenology‐focused adaptation strategies and actions. Twenty studies demonstrated shifts in timing of regional marine organisms and seasonal environmental events. The most common response was earlier timing, observed in spring onset, spring and winter hydrology, zooplankton abundance, occurrence of several larval fishes, and diadromous fish migrations. Later timing was documented for fall onset, reproduction and fledging in Atlantic puffins, spring and fall phytoplankton blooms, and occurrence of additional larval fishes. Changes in event duration generally increased and were detected in zooplankton peak abundance, early life history periods of macro‐invertebrates, and lobster fishery landings. Reduced duration was observed in winter–spring ice‐affected stream flows. Two studies projected phenological changes, both finding diapause duration would decrease in zooplankton under future climate scenarios. Phenological responses were species‐specific and varied depending on the environmental driver, spatial, and temporal scales evaluated. Overall, a wide range of baseline phenology and relevant modeling studies exist, yet surprisingly few document long‐term shifts. Results reveal a need for increased emphasis on phenological shifts in the Gulf of Maine and identify opportunities for future research and consideration of phenological changes in adaptation efforts.

Copepod diapause and the biogeography of the marine lipidscape - Nicholas R. Record; Rubao Ji; Frédéric Maps; Øystein Varpe; Jeffrey A. Runge; Colleen M. Petrik; David Johns (Journal of Biogeography, 2018)
Aim One of the primary characteristics that determines the structure and function of marine food webs is the utilization and prominence of energy‐rich lipids. The biogeographical pattern of lipids throughout the ocean delineates the marine “lipidscape,” which supports lipid‐rich fish, mammal, and seabird communities. While the importance of lipids is well appreciated, there are no synoptic measurements or biogeographical estimates of the marine lipidscape. Productive lipid‐rich food webs in the pelagic ocean depend on the critical diapause stage of large pelagic copepods, which integrate lipid production from phytoplankton, concentrating it in space and time, and making it available to upper trophic levels as particularly energy‐rich wax esters. As an important first step towards mapping the marine lipidscape, we compared four different modelling approaches of copepodid diapause, each representing different underlying hypotheses, and evaluated them against global datasets. Location Global Ocean. Taxon Copepoda. Methods Through a series of global model runs and data comparisons, we demonstrated the potential for regional studies to be extended to estimate global biogeographical patterns of diapause. We compared four modelling approaches each designed from a different perspective: life history, physiology, trait‐based community ecology, and empirical relationships. We compared the resulting biogeographical patterns and evaluated the model results against global measurements of copepodid diapause. Results Models were able to resolve more than just the latitudinal pattern of diapause (i.e. increased diapause prevalence near the poles), but to also pick up a diversity of regions where diapause occurs, such as coastal upwelling zones and seasonal seas. The life history model provided the best match to global observations. The predicted global biogeographical patterns, combined with carbon flux estimates, suggested a lower bound of 0.031–0.25 Pg C yr −1 of downward flux associated with copepodid diapause. Main conclusions Results indicated a promising path forward for representing a detailed biogeography of the marine lipidscape and its associated carbon flux in global ecosystem and climate models. While complex models may offer advantages in terms of reproducing details of community structure, simpler theoretically based models appeared to best reproduce broad‐scale biogeographical patterns and showed the best correlation with observed biogeographical patterns.

Quantifying Tradeoffs for Marine Viruses - Nicholas R. Record; David Talmy; Selina Våge (Frontiers in Marine Science, 2016)

Observed forest sensitivity to climate implies large changes in 21st century North American forest growth - Noah D. Charney; Flurin Babst; Benjamin Poulter; Sydne Record; Valerie M. Trouet; David Frank; Brian J. Enquist; Margaret E. K. Evans (Ecology Letters, 2016)
Predicting long‐term trends in forest growth requires accurate characterisation of how the relationship between forest productivity and climatic stress varies across climatic regimes. Using a network of over two million tree‐ring observations spanning North America and a space‐for‐time substitution methodology, we forecast climate impacts on future forest growth. We explored differing scenarios of increased water‐use efficiency ( WUE ) due to CO 2 ‐fertilisation, which we simulated as increased effective precipitation. In our forecasts: (1) climate change negatively impacted forest growth rates in the interior west and positively impacted forest growth along the western, southeastern and northeastern coasts; (2) shifting climate sensitivities offset positive effects of warming on high‐latitude forests, leaving no evidence for continued ‘boreal greening’; and (3) it took a 72% WUE enhancement to compensate for continentally averaged growth declines under RCP 8.5. Our results highlight the importance of locally adapted forest management strategies to handle regional differences in growth responses to climate change.

Fungal biotransformation of p-coumaric acid into caffeic acid by Pycnoporus cinnabarinus: an alternative for producing a strong natural antioxidant - Isabel Estrada Alvarado; David Navarro; Eric Record; Michèle Asther; Marcel Asther; Laurence Lesage-Meessen (World Journal of Microbiology and Biotechnology, 2003)